2006
DOI: 10.1007/s11055-006-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Features of the expression of the c-Fos gene along the rostrocaudal axis of the hippocampus in common voles after rapid training to solve a spatial task

Abstract: The level of expression of the c-Fos protein in neurons was used as a measure of the activation of transcription in the hippocampus of common voles (Microtus arvalis Pall.) after rapid spatial training. Stained Fos-positive cells were counted on 20 brain sections along the rostrocaudal axis of the hippocampus. Voles were trained to find the exit to their home cages through one of the arms of a modified eight-arm radial maze (using a 2-h series of six trials on one day). Animals were initially trained to leave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Expression of some IEGs, for example c-fos , zif268 and arc , is induced in animals through a new experience and plays a key role in plastic rearrangements and the formation of long-term memory, storing the individual experience [ 1 , 3 , 5 , 6 ]. These properties of IEGs form the basis for the methods of immunohistochemical and in situ hybridization mapping of the brain, which make it possible to identify the cognitive neural networks activated during learning [ 2 , 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of some IEGs, for example c-fos , zif268 and arc , is induced in animals through a new experience and plays a key role in plastic rearrangements and the formation of long-term memory, storing the individual experience [ 1 , 3 , 5 , 6 ]. These properties of IEGs form the basis for the methods of immunohistochemical and in situ hybridization mapping of the brain, which make it possible to identify the cognitive neural networks activated during learning [ 2 , 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plausible gene expression differences were analyzed as well Steinberger et al, 2003, among others). Using the technique of early gene expression in the mouse brain, it was demonstrated that distinct and simultaneously working plasticity mechanisms are active during different phases of the Morris water maze training (Laeremans et al, 2014). The differential involvement of rostral and caudal hippocampal areas in spatial "knowledge" formation was demonstrated as well , 2011.…”
Section: Radial and Water Maze Eramentioning
confidence: 99%
“…Therefore, it was natural to suppose that neuronal memory is also associated with a similar mechanism and that acquisition 6 The long-term changes in neuronal firing produced by instrumental learning occur in the same areas of the rat cerebral cortex [1203] and forebrain of chicks [1040], where the transcription was activated during acquisition of the same task. During learning, content of myscarinic cholinergic receptors in specific area of brain increases [1040,53], synthesis of proteins and ribonucleic acid (RNA) increases [574,768], expression of early genes (which ensure activation of other genes and thus regulate the order of protein synthesis) strengthens [42,690] and the system of second messenger cyclic AMP is augmented [811,20,86]. Brain areas where neuronal activity is correlated with learning are narrowed after fastening of habits [1094,489,561].…”
Section: Chemical Traces Of Memory and Chemical Sensitivity Of Memorymentioning
confidence: 99%